Trend Rumor dan Peran Dividen pada Volatilitas Saham - Putri, Rahmawati Nur Wida; Alfa Rahmiati (Owner : Riset dan Jurnal Akuntansi, 2024)
Aiming to compare 12 literatures, both studies conducted in Indonesia and abroad which previously existed in the period 2012 to 2018. Articles published in reputable journals SINTA 1-3 and on an international scale. This article is a literature review that discusses rumor trends and the role of dividends in stock volatility. Not only discussing stock volatility theoretically, this study also compares how dividends affect stock volatility that has been studied so far, using what models and methods. The limitation of this research is that it only focuses on dividends and dividend policy and the effect of RUMP on stock volatility. Suggestions for further research to add to the literature with a focus on other variables such as company size, leverage.